2018
DOI: 10.1111/cdev.13103
|View full text |Cite
|
Sign up to set email alerts
|

Family Turbulence and Child Internalizing and Externalizing Behaviors: Moderation of Effects by Race

Abstract: This study examined the impact of residential instability and family structure transitions on the development of internalizing and externalizing problems from age 2 through 10.5. Child's race was examined as a moderator. Caregiver reports of internalizing and externalizing behaviors were obtained on 665 children at ages 5 and 10.5. Early-childhood residential and family structure transitions predicted elevated internalizing and externalizing problems at ages 5 and 10.5, but only for Caucasian children. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Du yasong et al showed that family structure and environment were closely related to children's behavioral development [22], and LBC as special family structure will have more emotional [23] and social behavior problems [24].Existing results showed a sizable adverse effect of exposure to parental migration on the health and education outcomes of children [25].Numerous studies have shown that parental migration has a negative impact on EBP in children [23,[26][27][28][29][30][31]. Some research showed that changes in family structure in early childhood [32], poor family communication and decreased maternal positive reappraisal [33]were statistically associated with children's later elevated EBP. Another study found children exposed to maternal intimate partner violence (IPV)were more likely to have borderline to clinical level scores on EBP [34].…”
Section: Introductionmentioning
confidence: 99%
“…Du yasong et al showed that family structure and environment were closely related to children's behavioral development [22], and LBC as special family structure will have more emotional [23] and social behavior problems [24].Existing results showed a sizable adverse effect of exposure to parental migration on the health and education outcomes of children [25].Numerous studies have shown that parental migration has a negative impact on EBP in children [23,[26][27][28][29][30][31]. Some research showed that changes in family structure in early childhood [32], poor family communication and decreased maternal positive reappraisal [33]were statistically associated with children's later elevated EBP. Another study found children exposed to maternal intimate partner violence (IPV)were more likely to have borderline to clinical level scores on EBP [34].…”
Section: Introductionmentioning
confidence: 99%
“…In recognizing the importance of understanding the determinants of early behavior problems, a growing body of research has focused on elucidating family risk factors. In particular, family instability, characterized by the cumulative amount of transitions experienced by the family (e.g., caregiver intimate relationship transitions, caregiver changes, residential moves, or caregiver income/job loss), has been identified as a consistent precursor of externalizing symptoms in childhood (e.g., Ackerman, Kogos, Youngstrom, Schoff, & Izard, 1999; Cavanagh & Huston, 2006; Milan, Pinderhughes, & Conduct Problems Prevention Research Group, 2006; Womack, Taraban, Shaw, Wilson, & Dishion, 2018). Because early childhood is a time when children are actively forming expectations about the consistency of their care and relationships with significant figures in their lives (Sroufe, 2000), instability experienced during this developmental period may have an especially pronounced impact on children's adjustment outcomes (Belsky, Schlomer, & Ellis, 2012).…”
mentioning
confidence: 99%
“…A previous study reported that parental migration had a negative impact on IBP in children [25]. Some research has shown that changes in family structure in early childhood [26], poor family communication and decreased maternal positive reappraisal [27] were statistically associated with children's later elevated IBP. However, limited research has focused on studying internalizing problems in hui nationality LBC, and there is still a lack of research with large sample sizes that could reveal the actual background of IBP in these children.…”
Section: Introductionmentioning
confidence: 96%